Reproductive Biology of Female Pacific Halibut (Hippoglossus stenolepis) in the Gulf of Alaska - Fish, Teresa; Wolf, Nathan; Smeltz, Timothy Scott; Harris, Bradley P.; Planas, Josep V. (Frontiers in Marine Science, 2022)
Developing a robust understanding of Pacific halibut reproductive biology is essential to understanding recent stock declines and refining current management strategies. This is especially true in the face of large-scale environmental changes to which spawning fish are particularly vulnerable. For Pacific halibut, reproductive studies have principally focused on population or regional scales, leaving the specific details of organism-level reproductive development unexamined. The work described here aims to address information gaps in Pacific halibut reproductive biology by conducting a detailed examination of the annual reproductive cycle with special attention to reproductive and physiological indicators (e.g. oocyte diameter, gonadosomatic index, hepatosomatic index, Fulton’s condition factor, somatic fat) and their use in characterizing female developmental stages and reproductive phases. Through a detailed examination of temporal changes in reproductive characteristics, as well as developmental stages and reproductive phases, our results provide important biological inputs for improving our understanding of stock dynamics and may allow for refined management as the effects of global environmental change increase in high latitude waters.